PERENCANAAN PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMH) KARANGTALUN, KABUPATEN TEMANGGUNG - Rahmat Ramadhany Aprilianto; Achmad Fungkas; Sri Eko Wahyuni; Suharyanto Suharyanto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Generally in remote rural areas, especially in the Temanggung regency Karangtalun are difficult to reach PLN's electrical supply but have the potential for huge energy of river water, then it can be utilized by the construction of Pembangkit Listrik Tenaga Mikrohidro (PLTMH) for rural electricity needs can be fulfilled with the population evenly so that no society can not feel the electricity in the place they live in this modern era. In areas that are Logung river on the border between Kendal and Temanggung regency that have the potential of water (Q) of 1,30 m3/sec with a 15 m high waterfall. Then it can generate power for the turbine at 137,85 Kw with the type of cross flow turbine capable to power in the Karangtalun as many as 153 homes. The costs incurred for the development of Pembangkit Listrik Tenaga Mikrohidro (PLTMH) Karangtalun Rp. 11.859.530.000,00 with construction work for 91 weeks.